2020
DOI: 10.21203/rs.3.rs-65497/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adverse events in cardiovascular disease patients taking clopidogrel: impact of CYP2C19 genotype polymorphisms

Abstract: Background: Clopidogrel combined with aspirin in antiplatelet therapy is the first-line clinical regimen for cardiovascular diseases. The CYP2C19 gene influences the absorption and metabolism of clopidogrel and its polymorphisms affect antiplatelet therapy drug efficacy, which may lead to adverse events including stent thrombosis and haemorrhage. The main objective of this study was to explore the impact of CYP2C19 polymorphisms on adverse events in cardiovascular disease patients.Methods:We recruited 350 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
0
1
Order By: Relevance
“…Similar findings were obtained in a study of patients treated with percutaneous coronary intervention (PCI) and dual antiplatelet therapy (DAPT), which indicated a significant link between main adverse cardiovascular events )MACE( and CYP2C19*2, but not CYP2C19*3 (25) . In contrast to the present study's findings, a study in Melbourne, Australia, found that CYP2C19*17 carriers had a higher risk of ischemia events (P=0.04), but CYP2C19*2 and CYP2C19*3 carriers had no significant association with the outcomes including ischemic events (28) . The explanation for the difference between these conflicting results and the findings of the present study , regarding the relation of CYP2C19*2 and *3 polymorphisms with the recurrent risk of stroke, is may be due to the difference in the allelic frequency between populations since it is highest in Asian populations compared to others (26) , as a result the low frequency of CYP2C19*2 and *3 in populations of Australia in the last study was not sufficient to make a strong correlation with the ischemic events.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar findings were obtained in a study of patients treated with percutaneous coronary intervention (PCI) and dual antiplatelet therapy (DAPT), which indicated a significant link between main adverse cardiovascular events )MACE( and CYP2C19*2, but not CYP2C19*3 (25) . In contrast to the present study's findings, a study in Melbourne, Australia, found that CYP2C19*17 carriers had a higher risk of ischemia events (P=0.04), but CYP2C19*2 and CYP2C19*3 carriers had no significant association with the outcomes including ischemic events (28) . The explanation for the difference between these conflicting results and the findings of the present study , regarding the relation of CYP2C19*2 and *3 polymorphisms with the recurrent risk of stroke, is may be due to the difference in the allelic frequency between populations since it is highest in Asian populations compared to others (26) , as a result the low frequency of CYP2C19*2 and *3 in populations of Australia in the last study was not sufficient to make a strong correlation with the ischemic events.…”
Section: Discussioncontrasting
confidence: 99%